2010
DOI: 10.1002/ange.201003662
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra and Hydrogen‐Bonded Network Structures of Large Protonated Water Clusters H+(H2O)n (n=20200)

Abstract: Exakt größenselektierte protonierte Wassercluster H+(H2O)n (n=20–200) wurden IR‐spektroskopisch untersucht, um Einblicke in die Strukturen ausgedehnter H‐verbrückter Wassernetzwerke zu erhalten. Die spektralen Eigenschaften zeigen, dass sich die Clusterstrukturen bei steigender Clustergröße nach und nach der Struktur des Volumenwasser‐Netzwerks angleichen und dabei die Zahl vierfach koordinierter Wassermoleküle wächst (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The bias towards donated rather than accepted hydrogen bonds, within the two-shell H 21 O 10 + ion cluster, requires that this hydrated ion must be surrounded by a zone of broken hydrogen bonds. This is confirmed by infrared spectra that show that the presence of an H 3 O + ion extends to affect the hydrogen bonding of at least 100 surrounding water molecules (Mizuse et al 2007). almost back to their values (95-98%) in the water molecule (Fig.…”
Section: Figure 5 the H 2 O With 'Free' Dangling O-h (A1) Held By Twmentioning
confidence: 80%
“…The bias towards donated rather than accepted hydrogen bonds, within the two-shell H 21 O 10 + ion cluster, requires that this hydrated ion must be surrounded by a zone of broken hydrogen bonds. This is confirmed by infrared spectra that show that the presence of an H 3 O + ion extends to affect the hydrogen bonding of at least 100 surrounding water molecules (Mizuse et al 2007). almost back to their values (95-98%) in the water molecule (Fig.…”
Section: Figure 5 the H 2 O With 'Free' Dangling O-h (A1) Held By Twmentioning
confidence: 80%
“…[2][3][4][5] The proton transfer reaction was most widely studied in various forms of water, i.e. in water clusters, [6][7][8][9][10][11][12][13][14][15][16][17] liquid water 18 or ices. 19,20 The proton transfer in water belongs among the fastest chemical processes -the estimates for the H2O + lifetime are below 100 fs.…”
Section: Introductionmentioning
confidence: 99%
“…The information on the amount of water available for the hydrolysis of silanes and subsequent condensation has been studied by several spectroscopic techniques, such as FTIR [27][28][29] , Raman [30][31] , UV-vis, NMR 32 , neutron scattering, etc. [33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, O-H band from hydrogen bonded water is analysed in the region between 3,200 and 3,800 cm -1 39 , while, in fingerprint region, the O-H bond appears between 940 and 980 cm -1 in silanol, between 910 and 930 cm -1 in epoxy and between 870 and 950 cm -1 in pure alcohols. Mizuse et al 28,40 in a series of articles demonstrated that O-H bond vibration frequency, intensity, peak shape and position vary as a function of water molecule clustering and the nature of the hydrogen bond existing with or between the clusters.…”
Section: Introductionmentioning
confidence: 99%